1977
DOI: 10.1002/cne.901720107
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of cutaneous type I mechanoreceptors (Haarscheiben) in cats following denervation

Abstract: Denervation of specialized cutaneous mechanoreceptors (Haarscheiben or domes) in cats was followed after 20 and 25 days by the following alterations in receptor structure: (1) reduced numbers of Merkel cells, (2) Merkel cells degenerating in situ, (3) fewer dense-core granules in the cytoplasm of Merkel cells, (4) an increased number of agranular dendritic cells and Langerhans cells in the dome, (5) the apparent phagocytosis of Merkel cells by Schwann and Langerhans cells, (6) fewer epithelial cell layers over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 43 publications
4
26
0
1
Order By: Relevance
“…A lot of papers on the Merkel cell have appeared during the last two decades (CAUNNA, 1962;MUNGER, 1965MUNGER, , 1977MUSTAKALLIO and KIISTALA, 1967;SMITH, 1967SMITH, , 1970IGGO and MUIR, 1969;KUROSUMI et al, 1969;BREATHNACH, 1971;LYNE and HOLLIS 1971;HASHIMOTO, 1972 a, b;ANDRES and DURING, 1973;NAFSTAD, 1971a, b;WINKELMANN and BREATHNACH, 1973;ENGLISH, 1974ENGLISH, , 1977WHEITEAR, 1974;BUDTZ and LARSEN, 1975;HALATA, 1975;SAXOD, 1978;TWEEDLE, 1978;TACHIBANA, 1978TACHIBANA, , 1979, and many others). But the life history, including the developmental origin, of the Merkel cell is not necessarily clear.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of papers on the Merkel cell have appeared during the last two decades (CAUNNA, 1962;MUNGER, 1965MUNGER, , 1977MUSTAKALLIO and KIISTALA, 1967;SMITH, 1967SMITH, , 1970IGGO and MUIR, 1969;KUROSUMI et al, 1969;BREATHNACH, 1971;LYNE and HOLLIS 1971;HASHIMOTO, 1972 a, b;ANDRES and DURING, 1973;NAFSTAD, 1971a, b;WINKELMANN and BREATHNACH, 1973;ENGLISH, 1974ENGLISH, , 1977WHEITEAR, 1974;BUDTZ and LARSEN, 1975;HALATA, 1975;SAXOD, 1978;TWEEDLE, 1978;TACHIBANA, 1978TACHIBANA, , 1979, and many others). But the life history, including the developmental origin, of the Merkel cell is not necessarily clear.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of Merkel Cell carcinoma as a sweat gland carcinoma by Toker in 1972 and the identification of neurosecretory granules by electron microscopy 25 confirming the neuroendocrine origin of the tumor, this neoplasm has been characterized in detail 1,4,15,20,21,23,26,27. The nearly exclusive appearence as primary skin tumor most common in the head and neck region (54%) followed by the lower limbs (27%) and the arms and trunk (19%) 12 is due to the distribution of the postulated cell of origin, the cutaneous Merkel cell 1,4.5,20,22,26 Although Merkel cells are also described to be present in the oral mucosa 6 the palate 29, only a few reports of Merkel cell carcinomas locations other than the skin have been published in recent years 9,14,17, 30.…”
Section: Discussionmentioning
confidence: 96%
“…Part of the lower labial mucosa was excised following mental nerve resection. (ENGLISH, 1974;OCHIAI, 1977;OCHIAI et al, 1979;TACHIBANA, 1979;ENGLISH et al, 1980;OCHIAI and SuzuKI, 1981;TACHIBANA and ISHIZEKI, 1981). However, the mechanism of differentiation of the Merkel cell is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that very little change occurred in the number and ultrastructure of Merkel cells after denervation (SMITH, 1966(SMITH, , 1967HARTSCHUH and WEIHE, 1977;BENKENSTEIN, 1979;TACHIBANA et al, 1982). On the other hand, other authors (PALMER, 1965;BURGESS et al, 1974;ENGLISH, 1977;KUROSUMI et al, 1979) have shown or suggested a marked decrease in the number of Merkel cells and the specific granules in Merkel cell following denervation, and elicited a supposition that some neurotrophic influence exists between the Merkel cell and the nerve terminal.…”
Section: Control Observations (Normal Labial Mucosa)mentioning
confidence: 99%